Second-hand smoke exposure at home and indoor work area among college students in Mangalore, South India - Praveen S Jodalli; Ganesh Shenoy Panchmal; R J Ancy; Amitha N Basheer (Wolters Kluwer Medknow Publications, 2021)
Background: Second-hand smoke (SHS) causes more than 1.2 million premature deaths per year and other serious diseases. Aim: The aim of the present study was to determine exposure to SHS among college students in Mangalore, South India. Methods: This cross-sectional study was done among 2063 college students aged 18-24 years in Mangalore. Data regarding exposure to SHS at home and indoor work areas were collected. Chi square test was used to test the association between study variables. Multinomial logistic regression was used to find factors influencing SHS exposure. Results: In the present study, 9.9% of the respondents were exposed to tobacco smoke at home of which 8.4% were nonsmokers. Among the respondents, 21.7% were exposed to tobacco smoke at indoor work areas of which 19.3% were nonsmokers. Significant association was found between current tobacco smoking status and anyone smoking inside the home or workplace. Logistic regression analysis revealed that males had 1.814 more odds of getting exposed to SHS at home and 1.976 more odds of getting exposed to SHS at indoor work areas than females. Conclusion: Exposure to SHS was higher at indoor work areas than at home and majority of the respondents exposed to SHS were nonsmokers. The findings emphasize the need for increased efforts to implement strategies to control SHS exposure.